2015
DOI: 10.1186/s12889-015-1520-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of pre-hypertension and hypertension among the adults in rural Bangladesh: findings from a community-based study

Abstract: BackgroundThe people of low and middle income countries bear about 80% of the global burden of diseases that are attributable to high blood pressure. Hypertensive people contribute half of this burden; the rest is among the people with lesser degrees of high blood pressure. Prehypertension elevates the risk of CVD, and that of end-stage renal disease. Bangladesh is a developing country, with more than 75% of the population live in rural area. This study aims to determine the prevalence and predictors of pre-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
40
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 38 publications
30
40
10
2
Order By: Relevance
“…10,16 Studies from other parts of the world report prevalence of hypertension to be lower than our findings. [17][18][19] Our study found the prevalence of hypertension was significantly higher among the males compared to females (p<0.001) which is consistent with other findings, 15,20,21 whereas others report higher prevalence of hypertension in females and difference was significant. 17 Our findings reveal that 46.6% of the study subjects were pre-hypertensive.…”
Section: Discussionsupporting
confidence: 90%
“…10,16 Studies from other parts of the world report prevalence of hypertension to be lower than our findings. [17][18][19] Our study found the prevalence of hypertension was significantly higher among the males compared to females (p<0.001) which is consistent with other findings, 15,20,21 whereas others report higher prevalence of hypertension in females and difference was significant. 17 Our findings reveal that 46.6% of the study subjects were pre-hypertensive.…”
Section: Discussionsupporting
confidence: 90%
“…Prehypertension is now recognized as an important candidate for cardiovascular intervention and risk reduction. 10 Numerous studies have been undertaken to assess the prevalence of hypertension. This study has assessed the prevalence of hypertension and also looks at the age profile of hypertensives and how blood pressure differs between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence varies widely from 1.21% to 32%. 11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2). According to the Bangladesh NCD Risk Factor Survey 2010 27 , the prevalence of hypertension is 17.9% in general, 18.5% in men and 17.3% in women.…”
Section: Methodsmentioning
confidence: 99%